Survival and growth performance of the japanese scallop Patinopecten yessoensis seeds produced in the upper tolerant temperature - Qtae, Jo; S., K. Lim; C., Lee; Y., G. Gong; Rahman, Mohammad Mustafizur; D., K. Kim; J., S. Lee; K., J. Park (2008)
The Japanese scallop (Patinopecten yessoensis), a cold-tolerant bivalve, is one of the key species cultured in suspension on the Gangwon coast of the East Sea (Sea of Japan). However, since the commencement of the scallop farming in early 1990s mass mortalities occurred most probably due to daily temperature variation during summer. The East Sea Fisheries Research Institute (ESFRI) monitored the scallop mortalities for years, finding that hatchery-based seeds are more resistant against the daily temperature variation than wild seeds. Noticeable difference of hatchery-based seeds from wild ones are maternal selection and higher temperature to which their larval lives are exposed. ESFRI established a method producing the scallop seeds in mass at elevated temperature 182higher than previous temperature and found it more effective for survival in the nursery and thereafter on-going growth.